Draft Third Five Year Plan 1961-66 (Volume IV) Transport and Communications Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1961)
For the purpose of opening the country and providing access to the colonisation areas, 49 miles of roads already surveyed, 41.30 miles of new roads in Middle and North Andaman's and 25 miles of new roads in Nicobars, were programmed for construction during the Second Plan Period. Consolidation of 18.5 miles of roads, first coat painting of 41 miles of roads and Second coat painting of 64 miles of roads in South Andaman's was also to be undertaken.
Andaman and Nicobar Administration